TGF-β mimic proteins form an extended gene family in the murine parasite Heligmosomoides polygyrus. Issue 5 (April 2018) - Smyth, Danielle J.; Harcus, Yvonne; White, Madeleine P.J.; Gregory, William F.; Nahler, Janina; Stephens, Ian; Toke-Bjolgerud, Edward; Hewitson, James P.; Ivens, Alasdair; McSorley, Henry J.; Maizels, Rick M.
Graphical abstract: Highlights: A new family of parasite-specific TGF-β mimics was identified. Members of the new family are secreted by larval and adult life cycle stages. The new family is distantly related to the Complement Control Protein family. We experimentally determined active family members and domains within the protein. Abstract: We recently reported the discovery of a new parasite-derived protein that functionally mimics the immunosuppressive cytokine transforming growth factor (TGF)-β. The Heligmosomoides polygyrus TGF-β Mimic ( Hp -TGM) shares no homology to any TGF-β family member, however it binds the mammalian TGF-β receptor and induces expression of Foxp3, the canonical transcription factor of both mouse and human regulatory T cells. Hp -TGM consists of five atypical Complement Control Protein (CCP, Pfam 00084) domains, each lacking certain conserved residues and 12–15 amino acids longer than the 60–70 amino acids consensus domain, but with a recognizable 3-cysteine, tryptophan, cysteine motif. We now report on the identification of a family of nine related Hp -TGM homologues represented in the secreted proteome and transcriptome of H. polygyrus . Recombinant proteins from five of the nine new TGM members were tested for TGF-β activity, but only two were functionally active in an MFB-F11 reporter assay, and by the induction of T cell Foxp3 expression. Sequence comparisons reveal that proteins with functional activity are similar or identical to Hp -TGM across the first three CCP domains, but more variable in domains 4 and 5. Inactive proteins diverged in all domains, or lacked some domains entirely. Testing truncated versions of Hp -TGM confirmed that domains 1–3 are essential for full activity in vitro, while domains 4 and 5 are not required. Further studies will elucidate whether these latter domains fulfill other functions in promoting host immune regulation during infection and if the more divergent family members play other roles in immunomodulation.